The Impact Of Sustainability Disclosure On The Transparency Of Financial Performance In Iraqi Banks - Mohammed Ahmed Mhmood; Ali Ibrahim Ahmed (International Journal of Economics, Commerce, and Management, 2024)
The aim of the research is to study the impact of sustainability disclosure on financial performance transparency by applying it to a sample of Iraqi banks listed on the Iraq Stock Exchange (Al-Ahli Bank of Iraq, Gulf Commercial Bank, Mansour Investment Bank, Baghdad Bank), and sustainability disclosure was measured through the index (social disclosures, environmental disclosures, economic disclosures), and to achieve the objectives and hypothesis of the research, (178) questionnaires were distributed to bank employees, while the multiple regression method was used to test the impact of sustainability disclosure on financial performance transparency, and the research results reached the existence of banks' disclosure of sustainability aspects in their reports, which increases the awareness, perception and confidence of users of these reports, and increases the transparency of their financial performance and efficiency, in addition to the fact that banks with high profitability are more likely to apply the sustainability report in order to increase the transparency of their financial performance, in addition to the bank's economic and financial capabilities and size, confirming its need to prepare sustainability disclosure reports in order to increase investor confidence, which in turn leads to increasing the transparency of sustainability disclosure and improving its financial performance.